The effects of the exchange rate changes on the current account balance in the Turkish economy - (:unkn) unknown (BILGESEL YAYINCILIK SAN & TIC LTD, 2012)
The ongoing floating exchange rate regime in Turkey since 2001 brings about both positive and negative impacts on the economy. Although, foreign exchange market relatively happens to retrieve stability TL strengthening has detrimental side effects on the current account balance in the Turkish Economy. The purpose of this study is to investigate the effects of the real effective exchange rate on the current account balance in the Turkish Economy for the period 2003:01-2010:12 by applying time series econometric analysis. In the study it is found that the real effective exchange rate inversely affects the current account balance in the long run, indicating Marshall-Lerner condition holds in the Turkish Economy in the long run. According to the impulse response results, the J-Curve effect exists in the Turkish Economy Thus, competitiveness oriented currency, monetary and fiscal policies must be efficiently designed and applied in the Turkish Economy to achieve sustainable current account balance path.
Keywords: Marshall-Lerner condition; J-Curve; the current account balance; the Turkish Economy; J-CURVE; TIME-SERIES; COINTEGRATION